Targeting Reversible Disassembly as a Mechanism of Controlling V-ATPase Activity - M. Kane, Patricia (Current Protein and Peptide Science, 2012)
Vacuolar proton-translocating ATPases (V-ATPases) are highly conserved proton pumps consisting of a peripheral membrane subcomplex called V1, which contains the sites of ATP hydrolysis, attached to an integral membrane subcomplex called Vo, which encompasses the proton pore. V-ATPase regulation by reversible dissociation, characterized by release of assembled V1 sectors into the cytosol and inhibition of both ATPase and proton transport activities, was first identified in tobacco hornworm and yeast. It has since become clear that modulation of V-ATPase assembly level is also a regulatory mechanism in mammalian cells. In this review, the implications of reversible disassembly for V-ATPase structure are discussed, along with insights into underlying subunit-subunit interactions provided by recent structural work. Although initial experiments focused on glucose deprivation as a trigger for disassembly, it is now clear that V-ATPase assembly can be regulated by other extracellular conditions. Consistent with a complex, integrated response to extracellular signals, a number of different regulatory proteins, including RAVE/rabconnectin, aldolase and other glycolytic enzymes, and protein kinase A have been suggested to control V-ATPase assembly and disassembly. It is likely that multiple signaling pathways dictate the ultimate level of assembly and activity. Tissue-specific V-ATPase inhibition is a potential therapy for osteoporosis and cancer; the possibility of exploiting reversible disassembly in design of novel V-ATPase inhibitors is discussed.
Keywords: ATP hydrolysis